Cold atmospheric plasma delivery for biomedical applications. (April 2022) - Chen, Zhitong; Chen, Guojun; Obenchain, Richard; Zhang, Rui; Bai, Fan; Fang, Tianxu; Wang, Hanwen; Lu, Yingjie; Wirz, Richard E.; Gu, Zhen
Graphical abstract: Abstract: As the fourth state of matter, plasma's unique properties and interactions with other states of matter offer many promising opportunities for investigation and discovery. In particular, cold atmospheric plasma (CAP), operating at atmospheric pressure and room temperature, has remarkable potential for biomedical applications through various delivery methods. These biomedical applications include sterilization, wound healing, blood coagulation, oral/dental diseases treatment, cancer therapy, and immunotherapy. Effective delivery of plasma constituents is critical to its efficacy for these applications. Therefore, this review presents the key research activities related to CAP delivery (including direct CAP delivery, delivery of plasma-activated media, biomedical device-assisted plasma delivery, and CAP delivery with other therapeutics) and needs for future research. This review will be of great interest for understanding the current state-of-the-art of biomedical applications of plasma medicine while also giving researchers from a broad range of communities insight into research efforts that would benefit from their contributions. Such communities include biomedicine, physics, biochemistry, material science, nanotechnology, and medical device manufacturing.